Effect of Immersive Technology on Students’ Creativity: A Meta-Analysis - Juan Xiong; JianLin Wen; Xu Han; Wei Cui; GuangShu Pei; Zi Tao (SAGE Open, 2025)
In recent years, immersive technology has become increasingly popular in educational settings. Its immersive characteristics enhance learning achievement, boost motivation, promote skills, and foster students’ creativity. This meta-analysis synthesizes 19 researches published between 2012 and 2023 that examined the influence of immersive technology on students’ creativity. The findings indicate that immersive technology interventions significantly and positively affect students’ creativity, with a substantial effect size of 0.82. Given the high heterogeneity among the reviewed studies, factors such as country, educational level, treatment duration, type of immersive technology, and teaching activities were identified as moderating variables. The results suggest that immersive technologies can significantly enhance students’ creativity by transforming the educational experience. However, it is also important to recognize the temporal impact of these technologies, as excessive use may lead to physical discomforts that could impede the creative process. Studies demonstrate that in educational experiments aimed at enhancing student creativity through immersive technology, student-centered pedagogical approaches are essential. Nevertheless, the guidance of teachers remains indispensable to maximize the positive effects of immersive technologies on student’s creativity. This Meta-analysis is registered as INPLASY202210108.